2020
DOI: 10.1093/mnras/staa2583
|View full text |Cite
|
Sign up to set email alerts
|

HORuS transmission spectroscopy of 55 Cnc e

Abstract: HORuS is a new high-resolution echelle spectrograph available on the 10.4 m GTC. We report on the first HORuS observations of a transit of the super-earth planet 55 Cnc e. We investigate the presence of Na i and Hα in its transmission spectrum and we explore the capabilities of HORuS for planetary transmission spectroscopy. Our methodology leads to residuals in the difference spectrum between the in-transit and out-of-transit spectra for the Na i doublet lines of (3.4 ± 0.4) × 10−4, which sets an upper limit t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
3
13
2
Order By: Relevance
“…Our non-detection of H agrees with previous investigations not finding evidence of hydrogen absorption for this planet (Ehrenreich et al 2012;Tabernero et al 2020). Other absorption signatures from species with strong opacities previously resolved on gaseous exoplanets such as Mg (Cauley et al 2019), K (Keles et al 2019) or Ca (Yan et al 2020) are not detected either for 55 Cnc e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our non-detection of H agrees with previous investigations not finding evidence of hydrogen absorption for this planet (Ehrenreich et al 2012;Tabernero et al 2020). Other absorption signatures from species with strong opacities previously resolved on gaseous exoplanets such as Mg (Cauley et al 2019), K (Keles et al 2019) or Ca (Yan et al 2020) are not detected either for 55 Cnc e.…”
Section: Discussionsupporting
confidence: 91%
“…The non-detection of water (Esteves et al 2017;Jindal et al 2020) with the non-detection of light elements (Ehrenreich et al 2020;Zhang et al 2021) seems to make the water envelope scenario unlikely. A detectable thin silicate-vapor atmosphere scenario can not be strengthened either by Tabernero et al (2020) who did not find evidence for Na absorption or by this work not finding evidence of absorption for a variety of species. Overall, our work provide indications that favor the heavyweight atmospheric scenario.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…G64-12 was observed with HORuS (Tabernero et al 2020; at GTC 1 on March 11 and July 2, 2019, HD122563 on January 13th 2020; and SDSS 134338 was observed on December 3, 2019. Data reduction was carried out with the chain 2 , which performs bias and flatfield correction, order tracing, extraction, and wavelength calibration.…”
Section: Horusmentioning
confidence: 99%
“…Assuming the planet is a black body with zero albedo, we estimated an equilibrium temperature of T eq = 1617 ± 41 K. As such, it is likely that TOI-500 b does not have a primary atmosphere inherited from the formation process and has undergone complete photo-evaporation during the formation and evolution processes [17]. The extreme vicinity to the host star could also have caused the formation of a metallic (secondary) atmosphere, possibly via volcanic out-gassing, as it might have happened on 55 Cancri e (see [19] for the estimated upper limit of atmospheric composition, and also [20]) and for planet Earth. A statistical analysis of the atmospheric predicted signal-to-noise (S/N) ratio of Earth-sized planets thus far discovered showed that TOI-500 b stands among the top 10 objects, meaning it is a promising target to perform atmospheric studies with current and future instruments (see Methods and Figure 9).…”
Section: Main Textmentioning
confidence: 99%